2015
DOI: 10.1016/j.neuropsychologia.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of KIBRA and CLSTN2 genetic polymorphisms on cross-sectional and longitudinal measures of memory performance and hippocampal volume in older individuals

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. AbstractThe variability of episodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…Other studies have found larger hippocampal volumes for T carriers compared to CC homozygotes ( Palombo et al, 2013 ; Witte et al, 2016 ). A recent longitudinal study of older adults failed to detect differential hippocampal volume decline over a 2-year period in T carriers and CC homozygotes ( Boraxbekk et al, 2015 ). Few studies have examined regional brain volumes other than the hippocampus (for example, Wang D. et al, 2013 examined frontal and posterior cingulate regions associated with the default mode network), but to the best of our knowledge, no studies have examined this issue using voxel-based whole brain methods.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies have found larger hippocampal volumes for T carriers compared to CC homozygotes ( Palombo et al, 2013 ; Witte et al, 2016 ). A recent longitudinal study of older adults failed to detect differential hippocampal volume decline over a 2-year period in T carriers and CC homozygotes ( Boraxbekk et al, 2015 ). Few studies have examined regional brain volumes other than the hippocampus (for example, Wang D. et al, 2013 examined frontal and posterior cingulate regions associated with the default mode network), but to the best of our knowledge, no studies have examined this issue using voxel-based whole brain methods.…”
Section: Introductionmentioning
confidence: 97%
“…As an example, Almeida et al (2008) found that KIBRA allele variants have minimal impact once significant cognitive decline is evident among older adults, presumably due to incipient neurodegenerative disease. KIBRA studies have increasingly matched allele groups on some of the major factors that may negatively impact memory performance among older adults ( Wersching et al, 2011 ; Boraxbekk et al, 2015 ; Witte et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcβ appears to have acquired other functions during evolution ( Pettem et al , 2013 ; Um et al , 2014 ; Wang et al , 2014 ), and Alcβ can also interact with kinesin-1 ( Kawano et al , 2012 ). Alcγ expression may be lower in adults than expression of Alcα and Alcβ ( Hata et al , 2011 ), but Alcγ also binds kinesin-1 and may be involved in memory performance and cognition ( Boraxbekk et al , 2015 ; Lipina et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also more recent studies investigated the role of rs17070145 in memory performance in different population samples, reporting contrasting results. (Muse et al, 2014; Franks et al, 2014; Boraxbekk et al, 2015; Witte et al, 2016). Muse et al (2014) studied the correlation between rs17070145 and scores in cognitive tests in a Caucasian sample, detecting an association between better delayed recall performance in the T-carriers versus the C/C carries.…”
Section: Introductionmentioning
confidence: 99%